PERENCANAAN PENGGUNAAN PLTS DI STASIUN KERETA API CIREBON JAWA BARAT - Redaksi Tim Jurnal (Sekolah Tinggi Teknik PLN, 2017)
Utilization of solar cell technology as a source of electrical energy in Indonesia is still not well developed whereas Indonesia is located on the equator so it gets abundant sunshine. Technology should be maintained for the future of technology is environmentally friendly, one PLTS. SPP is a power generation system that converts solar energy into electricity through a photovoltaic module that is included in the green energy to become a renewable generator. The results show for the time being the use of solar systems, especially at the train station to meet its electricity needs not be economically viable. This is due to the high investment cost of solar systems compared with the cost of electricity purchased from conventional sources. However, sensitivity analyzes carried outshowed solar systems became feasible in some conditions.